Penerapan Metode Fun Creative Learning dalam Meningkatkan Minat Belajar Siswa - Ariyani, Lia; Syarnubi, Syarnubi; Dewi, Mutia; Septia Fahiroh; Padli (PAI RAFAH, 2024)
The method used in this research is quantitative research with an experimental approach, using a one group pretest and post-test design. The population of this study was all students at SD Negeri 2 Kayuara, where the sample was 32 students in class IV B. Data collection techniques use observation, tests, questionnaires and documentation. Data analysis was carried out using the t-test. The results of the research show that the results of data analysis using the t-test on the pre-test data before the fun creative learning method was applied and the post-test data after the fun creative learning method was applied, namely the value of t0 = 9.46 is greater than t0 (both 5% significance level or 1%), 2.04 < 10.70 > 2.74. This means that the alternative hypothesis (Ha): "The application of the fun creative learning method in PAI subjects has a significant influence on the learning interest of class IV students at SD Negeri 2 Kayuara, Sekayu District" is accepted with the null hypothesis (HO) being rejected. The t-test results on the student interest in learning questionnaire data are because t0 = 9.46 is greater than t0 (either 5% or 1% significance level), 2.04 < 41.06> 2.74. So it can be concluded that the application of the fun creative learning method can increase students' interest in learning in Islamic Religious Education subjects in class IV B of SD Negeri 2 Kayuara, Sekayu District.